The Mediation of Financial Report Information Quality on Governance Based on Apparatus Competence and Internal Control Systems - Ahmad (www.amertainstitute.com, 2024)
This study aims to examine the intervening influence of the quality of financial report information on governance based on the competence of personnel and the internal control system in the Makassar City Government. The objective of this research is to analyse the direct and indirect effects between the independent, dependent, and intervening variables. The data collection techniques (instruments) used include observation, questionnaires, and documentation. The population in this study comprises 44 regional work units (SKPD) in the Makassar City Government, consisting of 687 individuals selected purposively. The sample size of 268 respondents was determined using the Solving formula. Data analysis was conducted using Structural Equation Modelling (SEM) with the SmartPLS program. The results of the study indicate that competence has a significant effect on the quality of financial report information. The internal control system also has a significant effect on the quality of financial report information. However, competence does not significantly contribute to government governance. Similarly, the internal control system does not significantly enhance government governance. The quality of financial report information has a positive and significant impact on government governance. The findings suggest that improvements are needed in the competence area, particularly in enhancing independence in performing core duties and functions. Regarding the internal control system, there is a need for better implementation to identify the added value in each aspect of governance.